2007 IEEE Particle Accelerator Conference (PAC) 2007
DOI: 10.1109/pac.2007.4440197
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of burden resistors for high-precision DC current transducers

Abstract: The DC current transducer (DCCT) and accompanying A/D converter determine the precision of a power converter in accelerator operation. In the LHC context this precision approaches 10 -6 (1 ppm). Inside the DCCT a burden resistor is used to convert the current to an output voltage. The performance of this resistor is crucial for the accuracy, temperature behaviour, settling time and longterm drift of the DCCT. This paper reports on evaluations, a new parameter called "power coefficient" (PC) and test results fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Otherwise there is only one resistor type on the market offering the performance needed: Bulk Metal Foil or "foil". This technique, pioneered by Vishay, but now widely spread, tightly bonds a rolled metal foil to a substrate and seeks to compensate the resulting consistent stress effects as part of the overall resistor performance [86].…”
Section: Dccts (Direct-current Current Transformers)mentioning
confidence: 99%
“…Otherwise there is only one resistor type on the market offering the performance needed: Bulk Metal Foil or "foil". This technique, pioneered by Vishay, but now widely spread, tightly bonds a rolled metal foil to a substrate and seeks to compensate the resulting consistent stress effects as part of the overall resistor performance [86].…”
Section: Dccts (Direct-current Current Transformers)mentioning
confidence: 99%
“…The basic idea of the complementary pulse approach is to keep the current in the ratio networks constant, in order to safely neglect any dynamic effects (including the effect due to power coefficient [1]) therefore ensuring the performance of the system is independent from output pulse parameters. Once the ratio networks have reached a steady state thermal condition, the current is then steered from the DUT path (i OU T ) to a dummy path (i COM P ), as shown in Fig.…”
Section: Complementary Pulse Approachmentioning
confidence: 99%
“…In addition, this option would require multiple reference devices to satisfy requirements for different current ranges. The effect of thermal dynamics and power coefficient [1] are also a concern as it is difficult to estimate their impact for a pulsed application with such small duty cycles. A market survey of pulsed current sources concluded that none were available or completely satisfactory; the 100 A, 100 kHz transconductance amplifier based on NIST design [2], [3], which was also considered, has, indeed, an estimated temperature coefficient as high as 5 ppm / • C. As a consequence, a project was launched to develop this pulsed calibrator which also envisages a future use in faster applications.…”
Section: Introductionmentioning
confidence: 99%